(untitled) - Thomas, Hugh (New York, 1989)
The main purpose of this study is to provide a short history of the world arranged on thematic, rather than chronological, lines. At the end of the book it allowed to be drawn into a discussion of the crisis which appears to affect to the world in the last quater of twentieth century,...
Keywords: World history